Motivasi Masyarakat Bali Untuk Bekerja di Jepang - I Gusti Ayu Niken Launingtia (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
When working or doing something to be more enthusiastic, you must have a motivation, but increasing that motivation is a little difficult for some people. This research was conducted with the aim of knowing the motivation of the Balinese people to work in Japan. The object of this research is students who conduct job training at the Job Training Institute (LPK) in Ubud and Tabanan areas. The method of using the data in this study used the interview method, the observation method and the questionnaire method. The data analysis technique used is qualitative analysis technique. It can be concluded from the results of the analysis related to